The implementation of indonesia realistic mathematics learning approach (irml) to increase learning acchievement in the discussion painting and Corner splitting subject On the students grade viie smp negeri I seyegan - Tini Suhartini; Nanang Khuzaini (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2017)
The goals of this research are: (1) To describe the implementation of mathematics learning with realistic mathematics learning approach Indonesia (PMRI) in efforts to improve learning achievement of students in grade VII E SMP Negeri 1 Sayegan (2) describe the improvement of student achievement in mathematics graders VII E SMP Negeri 1 Sayegan through a realistic approach to learning mathematics Indonesia (PMRI). This research is a classroom action research conducted collaboratively with teachers. Subject of research is 32 students in grade VII E SMP Negeri 1 Sayegan. Collecting data using observation sheets, and about the avaluation of each cycle. The study was conducted in two cycles, the implementation of the first cycle obtained an average value of student achievement amounted to 83.00%, the second cycle obtained value student achievement by 93, 65%. Thus PMRI approach can improve student achievement.Keywords: Implementation Indonesia Mathematics Realistic Learning Approach(IMRL), learning achievement, mathematics Subjects.